Analisis Framing Pemberitaan Fatwa MUI tentang Boikot Produk Pro Israel di Media Kompas.com dan Republika.co.id - Ningrum, Gusmiana Cahya; Yusuf, Eka; Susanto, Tri (Jurnal Intervensi Sosial dan Pembangunan, 2025)
This research aims to understand how the framing analysis of the MUI's fatwa on the prohibition of pro-Israel products in the online media Kompas.com and Republika.co.id, displayed from November 10-19, 2023, is conducted. The theory used in this research is the framing analysis model by Zhongdang Pan and Gerald M. Kosicki, which consists of four structural devices: syntactic, script, thematic, and rhetorical. The results of this study indicate that there are differences in perspectives in framing news between Kompas.com and Republika.co.id. This can be seen as Kompas.com presents news that is neutral in nature and does not lean towards one side. Meanwhile, Republika.co.id in its reporting appears to be more pro-government, as in the fifth news article, Republika.co.id presents an invitation to join the boycott of pro-Israel products, with several entrepreneurs changing their raw materials. Keywords: Fatwa Haram, MUI, Boycott of Pro-Israel Products, Framing Analysis by Zhongdang Pan and Gerald M. Kosicki